The Role of Institutional Ownership Structure on Real Earnings Management in Growth Firms - Ponty SP Hutama; Sri Hastuti (AIBPM Publisher, 2021)
The objective of the study was to examine the role of institutional ownership structure on real earnings management on firms in growth stage. The real earnings management was indicated by three proxy such as abnormal CFO, abnormal discretionary expenses, and abnormal production costs. The sample of the study was the manufacturing firms listed in the Indonesia Stock Exchange. The data observation period was 5 years (2016-2020). Total samples are 600 firm-years. The samples are classified into various life cycle using dividend payout, sales growth, capital expenditure value, and age. The empirical results indicate concentration of institutional ownership affect the real earnings management through cash flow operating activities but this study cannot prove that the concentration of institutional ownership affects the real earnings management in firms that are in the growth stage. The findings prove the firms choose real earnings management through cash flow operating activities even though the cost is more in the long term.